Outdoor Learning and Play Pedagogical Practices and Children's Cultural Formation - Grindheim, Liv Torunn; Sørensen, Hanne Værum; Rekers, Angela (International Perspectives on Early Childhood Education and Development,, 2021)
This Open Access book examines children's participation in dialectical reciprocity with place-based institutional practices by presenting empirical research from Australia, Brazil, China, Poland, Norway and Wales. Underpinned by cultural-historical theory, the analysis reveals how outdoors and nature form unique conditions for children's play, formal and informal learning and cultural formation. The analysis also surfaces how inequalities exist in societies and communities, which often limit and constrain families' and children's access to and participation in outdoor spaces and nature. The findings highlight how institutional practices are shaped by pedagogical content, teachers' training, institutional regulations and societal perceptions of nature, children and suitable, sustainable education for young children. Due to crises, such as climate change and the recent pandemic, specific focus on the outdoors and nature in cultural formation is timely for the cultural-historical theoretical tradition. In doing so, the book provides empirical and theoretical support for policy makers, researchers, educators and families to enhance, increase and sustain outdoor and nature education.